Liquidity of European real estate equities: REITs and REOCs - Niskanen, Jaakko; Falkenbach, Heidi (International Journal of Strategic Property Management, 2012)
Listed real estate companies can be divided into two categories: real estate operating companies (REOCs) and real estate investment trusts (REITs). REOCs have been around for quite a while, whereas REITs are a somewhat new phenomenon in Europe, the main differences pertaining to permissible activities and taxation. This paper studies the relative differences of REOCs and REITs in terms of liquidity: Also asset returns, volatility and correlation to other equities are assessed. The liquidity tests performed reveal REITs to be significantly more liquid than REOCs, potentially due to restrictions regarding REIT ownership structure. Ceteris paribus, superior REIT liquidity implies REITs constitute a preferred investment vehicle.First Publish Online: 19 Jun 2012